A network analysis of postmigration living difficulties in refugees and asylum seekers - Benedikt Wicki; Tobias R. Spiller; Matthis Schick; Ulrich Schnyder; Richard A. Bryant; Angela Nickerson; Naser Morina (European Journal of Psychotraumatology, 2021)
Background: The prevalence of mental disorders among asylum seekers and refugees is elevated compared to the general population. The importance of post-migration living difficulties (PMLDs), stressors faced after displacement, has recently been recognized due to research demonstrating their moderating role of on mental health outcomes. Traditionally, PMLDs were investigated as count variables or latent variables, disregarding plausible interrelationships among them. Objectives: To use network analysis to investigate the associations among PMLDs. Methods: Based on a cross-sectional measurement of seventeen PMLDs in a clinical sample of traumatized asylum seekers and refugees (N = 151), a partial correlation network was estimated, and its characteristics assessed. Results: The network consisted of 71 of the 120 possible edges. The strongest edge was found between ‘Communication difficulties’ and ‘Discrimination’. ‘Loneliness, boredom, or isolation’ had highest predictability. Conclusion: Our finding of an association between communication difficulties and discrimination has been documented before and is of importance given the known negative impact of discrimination on mental and physical health outcomes. The high predictability of isolation is indicative of multiple associations with other PMLDs and highlights its importance among the investigated population. Our results are limited by the cross-sectional nature of our study and the relatively modest sample size.